(untitled) (Conferencea, 2022)
This article reveals the features of the preparation of the future teacher of primary education (BUNO). The article reveals the pedagogical conditions that contribute to increasing the effectiveness of the training of BUNO, discusses the specifics of the work of the school "Rivage" (Development) in the development of professional competence of BUNO. The scientific novelty of the study lies in the development of an organizational and methodological system for preparing students in the development of professional competence. As a result, four levels of students’ training (standard, algorithmic, heuristic, author’s) are identified and characterized, which are aimed at the gradual development of professional competence.